A crack-resistant strand wire and a strand twisting method for laser additive manufacturing of high-entropy alloys
Patent Information
- Application Number
- CN202610994071.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-10-09
AI Technical Summary
[0006]解决的技术问题:针对上述现有技术中电弧增材适用绞股丝难以满足激光急冷急热条件下的抗裂需求等问题,本发明提出一种用于激光增材制造高熵合金的抗裂纹绞股丝材及绞股方法,根据强度限定原则、弹性模量限定原则、熔点相近原则、成分限定原则、合金丝优先原则,设计绞股丝材的单丝构成和配置方式,保证绞股过程的稳定性,以及使用绞股丝材进行激光增材制造过程中具有良好的抗裂性能和成形质量
[0032]1. 本发明通过限定绞股丝材中铁、钴、镍、铬等主要元素的含量,并将铝、钛元素的质量分数之和控制在10%以下,使所形成的高熵合金以韧性较好的固溶体组织为主,在实现固溶强化和析出强化的同时,抑制过量铝、钛引起的硬脆相形成,从而降低激光快速凝固及重复热循环条件下的裂纹萌生和扩展倾向,提高激光增材构件的抗裂性能。
Smart Images

Figure CN122875982A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of additive manufacturing technology, specifically relating to a crack-resistant stranded wire and a stranding method for laser additive manufacturing of high-entropy alloys. This invention is particularly applicable to laser additive manufacturing processes using laser as a heat source and stranded wire as raw material, for preparing crack-free high-entropy alloy components. Background Technology
[0002] Compared to traditional alloys with only one or two main elements, high-entropy alloys, as a popular emerging material category, typically contain five or more main elements. This results in high configurational entropy and strong lattice distortion, despite being composed of simple solid solution phases. These characteristics contribute to the superior mechanical properties of high-entropy alloys, including high strength, high hardness, good wear resistance, and corrosion resistance. These properties make high-entropy alloys irreplaceable in high-end industrial fields such as aerospace, energy and power, and automotive manufacturing. In recent years, with the increasing demand for high performance in high-end equipment, high-entropy alloys have become a significant research hotspot in materials science and advanced manufacturing.
[0003] Additive manufacturing, as a revolutionary technology, can manufacture almost any complex geometry, eliminating the dependence on tools and molds in traditional processes. Laser additive manufacturing technology (including laser powder bed melting and laser directional energy deposition) is highly favored in high-end manufacturing fields due to its concentrated energy density, small heat-affected zone, low residual stress, and small deformation. Compared with arc additive manufacturing technology, laser additive manufacturing technology has significant advantages such as high forming accuracy and heat input, making it more suitable for the preparation of high-value complex components. However, the raw materials used in laser additive manufacturing are currently mainly divided into two types: powder and filament. Compared with powder, which has problems such as flammability, high cost, low utilization rate, and harsh storage conditions, filament shows advantages such as high safety, low cost, high deposition rate, high material utilization rate, and convenient storage. Using stranded filament as raw material can, to some extent, take into account the advantages of efficient and stable filament delivery and multi-element composition design, making it suitable for high-entropy alloy laser additive manufacturing.
[0004] However, some existing high-entropy alloy stranded wires are mainly used in arc additive manufacturing (such as CMT). But laser additive manufacturing and arc additive manufacturing differ significantly in heat source characteristics, molten pool size, cooling rate, and thermal cycling patterns. In particular, compared to an electric arc, lasers exhibit rapid heating and cooling, which makes alloys more prone to cracking during manufacturing, placing higher demands on the wire material. Therefore, the composition of high-entropy alloy stranded wire suitable for arc additive manufacturing may not be suitable for laser additive manufacturing.
[0005] Therefore, there is an urgent need to develop a crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys, which can ensure the low-cost and high-efficiency preparation of high-entropy alloy components in a safe environment, while also effectively preventing crack initiation during the additive manufacturing process and ensuring the quality of the forming. Summary of the Invention
[0006] Technical problem solved: Addressing the issue that existing technologies for arc additive manufacturing often fail to meet the crack resistance requirements under rapid heating and cooling conditions in laser processes, this invention proposes a crack-resistant stranded wire and stranding method for laser additive manufacturing of high-entropy alloys. Based on principles of strength limitation, elastic modulus limitation, similar melting point, composition limitation, and alloy wire priority, the invention designs the single-wire composition and configuration of the stranded wire to ensure the stability of the stranding process and to achieve good crack resistance and forming quality during laser additive manufacturing.
[0007] Technical Solution: The first objective of this invention is to provide a crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys. This crack-resistant stranded wire consists of a central wire and six peripheral wires evenly distributed around the edge of the central wire. The individual wires are twisted together by plastic deformation. Each individual wire has a tensile strength greater than 500 MPa, and the difference in melting point between the individual wires is less than 200°C. The peripheral wires are made of rigid materials with an elastic modulus greater than 100 GPa. The composition of the stranded wire meets the requirement that the proportions of iron, cobalt, nickel, and chromium are all greater than 15 wt%, and the sum of aluminum and titanium is less than 10 wt%. Furthermore, of the seven individual wires constituting the stranded wire, at most one is made of a single-element metal wire, while the rest are alloy wires.
[0008] The purpose of this invention is to provide a crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys. The stranded wire consists of one central wire and six outer wires, which are twisted together by the plastic deformation of the individual wires. By satisfying the principles of strength limitation, elastic modulus limitation, similar melting point, composition limitation, and alloy wire priority, the stability of the wire stranding process, as well as the crack resistance and forming quality during laser additive manufacturing, are ensured. The design principles of the stranded wire are as follows:
[0009] 1. Intensity Limitation Principle:
[0010] Each monofilament should have a tensile strength greater than 500 MPa to avoid breakage and local relaxation caused by insufficient monofilament strength during the stranding process, thereby improving the stability of the stranded structure.
[0011] 2. Principles for limiting the elastic modulus:
[0012] The six outer wires should be made of rigid materials (elastic modulus > 100 GPa) to ensure that the elastic modulus of the outer wire material is within the range of coordinated deformation, reduce local warping and stress concentration caused by excessive elasticity of the outer wires during stranding and additive manufacturing, and improve the stability of the strand structure and the consistency of wire feeding.
[0013] 3. Principle of similar melting points:
[0014] The melting point difference between each monofilament material should be less than 200℃ to ensure synchronous or near-synchronous melting during laser additive manufacturing, avoiding droplet instability and segregation caused by localized melting before or after melting, thereby reducing the initiation of pore cracks and improving forming quality.
[0015] 4. Ingredient limitation principle:
[0016] According to mass percentage, the nominal composition of twisted wire should meet the following requirements: the proportion of iron, cobalt, nickel, and chromium should all be greater than 15%, while the sum of aluminum and titanium should be less than 10%. Iron, cobalt, nickel, and chromium as the main elements are beneficial for forming a high-entropy alloy structure with face-centered cubic solid solution as the matrix phase, ensuring the alloy's toughness and forming stability. The addition of small amounts of aluminum and titanium can provide solid solution strengthening and precipitation strengthening, promoting alloy strength. However, excessive addition of aluminum and titanium will induce the formation of a large number of hard and brittle phases, which can become crack initiation sources during rapid laser solidification and repeated thermal cycling, increasing crack susceptibility. Therefore, this invention strictly controls the sum of the mass fractions of aluminum and titanium to below 10%, achieving a better balance between strength enhancement and crack resistance.
[0017] 5. Priority given to alloy wire:
[0018] Of the seven monofilaments constituting the stranded wire, only one is allowed to be made of a single-element material, while the remaining six are all made of pre-alloyed alloy wire. Utilizing the uniform composition and precisely controllable element ratios of the pre-alloyed wire, the problems of element segregation and phase separation that easily occur when multiple single-element wires melt simultaneously are avoided, significantly reducing the tendency for hot cracking and stress cracking caused by uneven molten pool composition during laser additive manufacturing. Retaining only one single-element wire allows for flexible control of the chemical composition, enabling small-range adjustments to the elemental proportions of the high-entropy alloy, thus balancing the stability of crack resistance with compositional flexibility.
[0019] As a preferred option, the composition of the crack-resistant stranded wire is as follows: Fe 26-30 wt%, Cr 14-20 wt%, Ni 29-33 wt%, Co 17-21 wt%, Al 0-4 wt%, Ti 4-8 wt%.
[0020] Preferably, the center wire is a 5545 nickel-titanium wire, and the outer wires are two 7030 nickel-chromium wires, two 255 iron-chromium-aluminum wires, one 4J29 iron-cobalt-nickel wire, and one cobalt wire.
[0021] Preferably, the same type of monofilament is placed in a centrally symmetrical position to ensure the balance of force and deformation during the twisting process, reduce local fluctuations during the twisting process, avoid local deformation, and thus improve the final forming quality of the twisted strand.
[0022] As a preferred option, the pure element metal content in the single metal wire is ≥99.5% to reduce the interference of impurity elements.
[0023] Preferably, the diameter of each monofilament is 0.4-0.8 mm to ensure that each monofilament has similar geometric dimensions and deformation response during the twisting process.
[0024] The second objective of this invention is to provide a stranding method for the above-mentioned crack-resistant stranded wire used in laser additive manufacturing of high-entropy alloys, the steps of which are as follows:
[0025] Step 1: Monofilament cleaning; Clean all monofilaments.
[0026] Step 2: Wire stranding: The stranded wire is stranded using a stranding device at a speed of 400-600 r / min and a twist pitch of 10-15 mm. Excessive stranding speed can lead to increased stress fluctuations and localized entanglement; while insufficient stranding speed affects production efficiency and makes it difficult to maintain stranding continuity. Furthermore, excessive twist pitch results in insufficient constraint during stranding, making subsequent strand unraveling more likely; insufficient twist pitch causes severe deformation of individual filaments and increases residual stress. Therefore, selecting the above-mentioned stranding speed and twist pitch range can simultaneously balance stranding efficiency and stability, ensuring the quality of the stranded wire.
[0027] Step 3, Post-processing: The twisted strands are ultrasonically cleaned and dried, and then vacuum-sealed and packaged.
[0028] Preferably, in step one, the cleaning method includes at least one of alkaline cleaning, ultrasonic cleaning, and electrolytic cleaning to remove surface oil, residual lubricant, oxide particles, and other impurities.
[0029] Preferably, in step two, the diameter of the twisted strands is 1.2-2.4 mm.
[0030] The third objective of this invention is to provide the application of the aforementioned crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys.
[0031] Beneficial effects:
[0032] 1. This invention limits the content of major elements such as iron, cobalt, nickel, and chromium in stranded wire, and controls the sum of the mass fractions of aluminum and titanium to below 10%, so that the resulting high-entropy alloy is mainly composed of a solid solution structure with good toughness. While achieving solid solution strengthening and precipitation strengthening, it suppresses the formation of hard and brittle phases caused by excessive aluminum and titanium, thereby reducing the tendency of crack initiation and propagation under rapid laser solidification and repeated thermal cycling conditions, and improving the crack resistance of laser additive components.
[0033] 2. The stranded wire material of this invention features similar melting points for each filament, a reasonable compositional distribution, and a stable wire feeding process. This reduces droplet oscillation, molten pool disturbance, and incomplete fusion caused by premature or delayed melting of some filaments, thus improving the continuity and stability of the molten pool. Simultaneously, it reduces unmelted particles, compositional segregation, and violent flow within the molten pool, lowering the probability of defects such as incomplete fusion, porosity, and cracks. This results in a high-entropy alloy deposition layer with a continuous surface, uniform microstructure, and fewer defects.
[0034] 3. The stranded filament of the present invention is formed by twisting one central filament and six peripheral filaments, which enhances the overall integrity of the filament and reduces the problems of dispersion, misalignment, and asynchronous feeding that easily occur when multiple single filaments are fed independently. Combined with the high rigidity constraint effect of the peripheral filaments, the stability of the filament is improved when passing through the feeding wheel, guide tube, and feeding nozzle, reducing slippage, strand breakage, and filament blockage.
[0035] 4. In this invention, of the seven monofilaments constituting the stranded wire, only one is allowed to be made of a single element; the remaining monofilaments are all made of pre-alloyed alloy wire. The pre-alloyed wire has a uniform element distribution and stable composition ratio, which reduces insufficient element diffusion, local enrichment, and phase separation phenomena that occur when multiple single elements are melted separately. This improves the chemical composition uniformity of the deposited layer and reduces the tendency for hot cracking and embrittlement caused by compositional inhomogeneity.
[0036] 5. In this invention, a 5545 nickel-titanium wire with an elastic modulus less than 100 GPa is designated as the center wire, and the remaining monofilaments with an elastic modulus greater than 100 GPa are designated as the outer wires. The high-stiffness outer monofilaments can provide stable constraint to the center wire, reducing local warping and excessive elastic deformation of the stranded wire during twisting, coiling, straightening, and feeding processes, thereby improving the overall straightness, dimensional stability, and consistency of the wire feeding trajectory.
[0037] 6. By rationally configuring the elastic modulus of the central and peripheral wires, and controlling the diameter of the single wire and the twist pitch, the deformation of each single wire can be coordinated during the twisting process, reducing local excessive bending and plastic deformation. At the same time, by controlling the content of hard and brittle phase-forming elements in high-entropy alloys, the local stress concentration caused by rapid temperature changes and microstructure transformation during laser additive manufacturing can be alleviated, thereby reducing residual stress and the resulting deformation and cracking risks.
[0038] 7. This invention selects monofilaments with tensile strength greater than 500 MPa, configures rigid materials with elastic modulus greater than 100 GPa as outer strands, and adopts monofilaments of equal diameter and the same type of monofilaments in a relative arrangement, so that each monofilament is subjected to balanced force and coordinated deformation during the stranding process, effectively reducing wire breakage, slack, eccentricity, cross-sectional distortion and local stress concentration; at the same time, controlling the stranding speed at 400-600 r / min and the twist pitch at 10-15 mm can avoid local entanglement, strand breakage and excessive deformation of monofilaments. While taking into account production efficiency, it improves the continuity of the stranding process, the structural stability and geometric consistency of the stranded wire, and ensures the wire feeding stability in the subsequent laser additive manufacturing process.
[0039] 8. This invention does not directly use stranded wire suitable for arc additive manufacturing. Instead, it takes into account the characteristics of laser additive manufacturing, such as high energy density, fast heating and cooling speed, small melt pool size and intense thermal cycling, and synergistically limits the strength, elastic modulus, melting point difference, chemical composition and number of single filaments, so that stranded wire can better adapt to the process conditions of laser additive manufacturing. Attached Figure Description
[0040] Figure 1 This is a front view of the high-entropy alloy stranded wire of the present invention;
[0041] Figure 2 This is a cross-sectional view of the high-entropy alloy stranded wire of the present invention;
[0042] Figure 3 This is a photograph of the high-entropy alloy stranded wire used in Embodiment 1 of the present invention.
[0043] Figure 4 This is a top view of the single-pass additive manufacturing morphology in Embodiment 2 of the present invention;
[0044] Figure 5 This is a cross-sectional view of a single-pass additive manufacturing process in Embodiment 2 of the present invention;
[0045] Figure 6 This is a phase distribution diagram of the high-entropy alloy EBSD in Example 2 of the present invention. Detailed Implementation
[0046] The present invention will be further described below with reference to the accompanying drawings and specific embodiments.
[0047] The composition and configuration of the twisted wires in the embodiments of this specification are as follows: Figure 1 and Figure 2As shown in Table 1, the key performance parameters of each monofilament are as follows. Among the monofilaments, the 4J29 iron-cobalt-nickel wire has the lowest tensile strength, but 550 MPa > 500 MPa, and all monofilaments meet the strength limitation principle; the maximum melting point difference between monofilaments is 110℃ < 200℃, which meets the principle of similar melting points; the strand composition is Fe28Cr16Ni31Co19Al1Ti5 (the numbers represent mass percentages), with cobalt, chromium, iron, and nickel all accounting for more than 15 wt%, and the sum of aluminum and titanium accounting for less than 10 wt%, which meets the composition limitation principle; of the 7 monofilaments constituting the strand, only 1 cobalt wire is a pure cobalt wire, and the other 6 are alloy wires, which meets the principle of priority for alloy wires.
[0048] Table 1 Key performance parameters of each monofilament
[0049]
[0050] Since the elastic modulus of 5545 nickel-titanium wire is 70 GPa < 100 GPa, it was selected as the center wire. The elastic modulus of the remaining monofilaments is all greater than 100 GPa, so they were selected as the outermost wires, and the same type of monofilaments were placed in symmetrical positions around the center. Therefore, the strand configuration ultimately conforms to the elastic modulus constraint principle.
[0051] Example 1
[0052] This embodiment describes the preparation of CoCrFeNiAlTi high-entropy alloy stranded wire, and the specific steps are as follows:
[0053] Step 1: Monofilament Preparation: Prepare 1.5 kg of 5545 nickel-titanium wire, 3 kg of 7030 nickel-chromium wire, 3 kg of 255 iron-chromium-aluminum wire, 1.5 kg of 4J29 iron-cobalt-nickel wire, and 1.5 kg of cobalt wire. Each type of monofilament has a diameter of 0.6 mm. The 3 kg of 7030 nickel-chromium wire and the 3 kg of 255 iron-chromium-aluminum wire are evenly divided into two parts, totaling seven coils of monofilament. The cobalt wire should have a cobalt content ≥99.5% to reduce interference from impurities.
[0054] Step 2, Monofilament Cleaning: Use alcohol to ultrasonically clean the surface of all monofilaments, ensuring that all filament surfaces are free of oil and impurities. After cleaning, avoid direct contact with the filament surface to prevent the introduction of secondary impurities.
[0055] Step 3, stranding the wire: according to... Figure 1The diagram shows the stranding of one 5545 nickel-titanium wire, two 7030 nickel-chromium wires, two 255 iron-chromium-aluminum wires, one 4J29 iron-cobalt-nickel wire, and one cobalt wire. The diameter of the stranded wires is 1.8 mm. The 5545 nickel-titanium wire is the center wire, with the two 7030 nickel-chromium wires, two 255 iron-chromium-aluminum wires, one 4J29 iron-cobalt-nickel wire, and one cobalt wire forming the outer layers. The two 7030 nickel-chromium wires and two 255 iron-chromium-aluminum wires are positioned relative to each other, and the individual wire arrangement is visible. Figure 2 The stranding speed is 550 r / min, and the twist pitch is 12.5 mm. The final strand length is approximately 600 m, and the finished strand is visible. Figure 3 .
[0056] Step 4, Post-processing: The twisted strands are ultrasonically cleaned and dried, and then vacuum-sealed and packaged.
[0057] Ultimately, this embodiment produced a 600 m long CoCrFeNiAlTi high-entropy alloy stranded wire. The wire composition was precisely designed by controlling the type and quantity of individual filaments. High cleanliness of the stranded wire was ensured through pre- and post-stranding cleaning and vacuum sealing packaging, guaranteeing the accuracy of the composition and the stability of the stranded wire in application. This invention is particularly suitable for rapidly obtaining high-entropy alloy wires with target compositions during experimental development and engineering verification stages.
[0058] Example 2
[0059] This embodiment uses the twisted wire prepared in Example 1 to perform single-pass laser additive manufacturing verification on a 304 stainless steel substrate. The specific steps are as follows:
[0060] First, the twisted wire was ultrasonically cleaned in anhydrous ethanol, and the surface of the 304 stainless steel substrate was also cleaned with anhydrous ethanol. Then, a single-pass additive manufacturing experiment of the CoCrFeNiAlTi high-entropy alloy was conducted using oscillating laser additive manufacturing technology. Specific parameters were: laser power 1.5 kW, wire feed speed 10 mm / s, scanning speed 10 mm / s, defocusing amount +5 mm, oscillation mode circular oscillation, oscillation frequency 50 Hz, oscillation amplitude 2.4 mm, and argon gas as the protective gas with a flow rate of 15 L / min. The obtained single-pass additive sample had a length of 110 mm, and its top view is shown below. Figure 4 As shown, the cross-section is as follows Figure 5 As shown. From a macroscopic morphology perspective, the sample exhibits a distinct and continuous fish-scale pattern, with good spreading and no obvious defects such as pores or cracks. This indicates that the twisted wire solution provided by this invention can maintain relatively stable wire feeding and achieve sufficient wire melting during laser additive manufacturing. Furthermore, as... Figure 6As shown, the microstructure of the high-entropy alloy is mainly an FCC+NiTi3 dual-phase structure (the matrix phase is the FCC phase, and the granular precipitate phase is the NiTi3 phase), and the second phase, NiTi3, is a hard and brittle phase with a content of less than 5%. This result demonstrates that the present invention has successfully controlled the content of the second phase precipitation through strict composition control, reducing the risk of cracking in the high-entropy alloy caused by excessive precipitate phase.
[0061] Comparative Example 1
[0062] Similar to the previous example, the difference is that the sample was prepared according to the composition shown in Table 2 in this comparative example. Since the mass percentage of cobalt is less than 15%, it does not meet the composition limitation principle. Single-pass laser additive manufacturing verification was performed on a 304 stainless steel substrate as in Example 2.
[0063] Table 2
[0064]
[0065] Comparative Example 2
[0066] Similar to the previous example, the difference is that the sample was prepared according to the composition shown in Table 3, and the mass percentage of cobalt was less than 15%, which does not meet the composition limitation principle. Single-pass laser additive manufacturing verification was performed on a 304 stainless steel substrate as in Example 2.
[0067] Table 3
[0068]
[0069] Crack observations were performed on Example 2 and Comparative Examples 1 and 2, and the results are shown in Table 4.
[0070] Table 4
[0071]
[0072] As shown in the table above, the twisted wire designed in this invention exhibits good formability and crack resistance in high-entropy alloy laser additive manufacturing.
[0073] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit them. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys, characterized in that, This crack-resistant stranded wire consists of a central wire and six peripheral wires evenly distributed around the edge of the central wire. The individual wires are twisted together by plastic deformation. Each individual wire has a tensile strength greater than 500 MPa and a melting point difference of less than 200℃. The peripheral wires are made of rigid materials with an elastic modulus greater than 100 GPa. The composition of the stranded wire meets the requirements that the proportions of iron, cobalt, nickel, and chromium must all be greater than 15 wt%, and the combined proportions of aluminum and titanium must be less than 10 wt%. Furthermore, of the seven individual wires constituting the stranded wire, at most one is made of a single metal wire, while the rest are made of alloy wire.
2. The crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys according to claim 1, characterized in that, The composition of the crack-resistant stranded wire is as follows: Fe 26-30 wt%, Cr 14-20 wt%, Ni 29-33 wt%, Co 17-21 wt%, Al 0-4 wt%, Ti 4-8 wt%.
3. The crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys according to claim 1, characterized in that, The central wire is a 5545 nickel-titanium wire, and the outer wires are two 7030 nickel-chromium wires, two 255 iron-chromium-aluminum wires, one 4J29 iron-cobalt-nickel wire, and one cobalt wire.
4. The crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys according to claim 3, characterized in that, The same type of monofilament is placed in a centrally symmetrical position.
5. The crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys according to claim 1, characterized in that, The pure element metal content in the single metal wire is ≥99.5%.
6. The crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys according to claim 1, characterized in that, Each monofilament has a diameter of 0.4-0.8 mm.
7. A stranding method for producing crack-resistant stranded wire for laser additive manufacturing of high-entropy alloys according to any one of claims 1-6, characterized in that, The steps are as follows: Step 1: Monofilament cleaning; Clean all monofilaments. Step 2, stranding the filaments: Use stranding equipment to strand the filaments at a speed of 400~600 r / min and a twist pitch of 10~15 mm. Step 3, Post-processing: The twisted strands are ultrasonically cleaned and dried, and then vacuum-sealed and packaged.
8. The stranding method for crack-resistant stranded wire used in laser additive manufacturing of high-entropy alloys according to claim 7, characterized in that, In step one, the cleaning method includes at least one of alkaline cleaning, ultrasonic cleaning, and electrolytic cleaning.
9. The stranding method for crack-resistant stranded wire used in laser additive manufacturing of high-entropy alloys according to claim 7, characterized in that, In step two, the diameter of the twisted strands is 1.2-2.4 mm.
10. The application of the crack-resistant stranded wire of any one of claims 1-6 in the laser additive manufacturing of high-entropy alloys.